EFFECT OF PROBIOTIC LACTOBACILLUS PARACASEI ON ASPERGILLUS FLAVUS GROWTH AND REDUCTION OF AFLATOXIN B1 IN VITRO - Al-Sandooq, Dhulfiqar; Hussein , H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to use of the probiotic Lactobacillus paracasei CNCMI-1572 to reduce the growth of the fungus Aspergillus flavus and determine its effect on the production or reduction of aflatoxin B1 through several treatments. All treatments (bacteria grown in MB and exposed to an ultrasonic device, bacterial filtrate exposed to ultrasonic, both treatments examined by FESEM to determine the final particle size, bacteria in MB only, bacterial filtrate only, all at concentrations of 1, 2, 3, 4, and 5%, and finally the treatment of solid MRS medium and bacteria with the fungus grown on it and incubated for seven days) showed significant differences in inhibiting fungal growth. The reduction of the toxin showed very high significant differences after measuring the concentration using HPLC technology. The last treatment was the best, showing no fungal growth with 100% inhibition and, consequently, no toxin production.